Cardiorespiratory fitness, body mass index, cardiovascular disease, and mortality in young men: A cohort study - Gorny, Alexander Wilhelm; Yap, Jonathan; Neo, Jia Wei; Chow, Wei En; Yeo, Khung Keong; Tan, Chuen Seng; Müller-Riemenschneider, Falk (Frontiers in Public Health, 2023)
Objective We examined the association between cardiorespiratory fitness (CRF), body mass index (BMI), incidence of major acute cardiovascular events (MACE), and all-cause mortality (ACM). Methods We conducted a retrospective cohort study involving 212,631 healthy young men aged 16 to 25 years who had undergone medical examination and fitness testing (2.4 km run) from 1995 to 2015. Information on the outcomes of major acute cardiovascular events (MACE) and all-cause mortality (ACM) were obtained from the national registry data. Results During 2,043,278 person-years of follow-up, 371 first MACE and 243 ACM events were recorded. Compared against the first run-time quintile, adjusted hazard ratios (HR) for MACE in the second to fifth quintiles were 1.26 (95% CI 0.84–1.91), 1.60 (95% CI 1.09–2.35), 1.60 (95% CI 1.10–2.33), and 1.58 (95% CI 1.09–2.30). Compared against the “acceptable risk” BMI category, the adjusted HRs for MACE in the “underweight,” “increased risk,” and “high-risk” categories were 0.97 (95% CI 0.69–1.37), 1.71 (95% CI 1.33–2.21), and 3.51 (95% CI 2.61–4.72), respectively. The adjusted HRs for ACM were increased in participants from the fifth run-time quintile in the “underweight” and “high-risk” BMI categories. The combined associations of CRF and BMI with MACE showed elevated hazard in the “BMI≥23-fit” category, which was more pronounced in the “BMI≥23-unfit” category. The hazards for ACM were elevated across the “BMI<23-unfit,” “BMI≥23-fit,” and “BMI≥23-unfit” categories. Conclusion Lower CRF and elevated BMI were associated with increased hazards of MACE and ACM. A higher CRF did not fully compensate for elevated BMI in the combined models. CRF and BMI remain important targets for public health intervention in young men.